2009
DOI: 10.3171/2009.6.spine0949
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of a ball-and-socket cervical disc prosthesis with cranial geometric center

Abstract: Object Few biomechanical in vitro studies have reported the effects of disc replacement on motion and kinematics of the cervical spine. The purpose of this study was to analyze motion through 3D load-displacement curves before and after implantation of a ball-and-socket cervical disc prosthesis with cranial geometric center; special focus was placed on coupled motion, which is a well-known aspect of normal cervical spine kinematics. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…7 Stress distribution in the implants segment unit, and the previous studies concluded that TDR could maintain kinematic motion [23,24]. In the present study, TDR with the ball-in-socket sliding articulationdesigned artificial disc of Prodisc-C had well demonstrated its function as reflected by the maintained spinal kinematic motion in the operative site.…”
Section: Discussionsupporting
confidence: 48%
“…7 Stress distribution in the implants segment unit, and the previous studies concluded that TDR could maintain kinematic motion [23,24]. In the present study, TDR with the ball-in-socket sliding articulationdesigned artificial disc of Prodisc-C had well demonstrated its function as reflected by the maintained spinal kinematic motion in the operative site.…”
Section: Discussionsupporting
confidence: 48%
“…Accordingly, due to conflicting information, surgeons face difficulties with the selection of appropriate indications and the type and size of implants [20,21]. Ex vivo motion studies and finite element studies have provided insight into the function of different CDR designs [4,38]. Unfortunately, laboratory studies are limited and cannot completely simulate the complex coupled in vivo motions during cervical spine activities, so patient-based research is required.…”
Section: Introductionmentioning
confidence: 99%
“…CDRs offer a varying degree of mobility and can be further stratified into constrained, semi-constrained and minimally/non-constrained ( Fig. 1) [4,20,21,25,30,31]. With constrained devices motion is less than that seen physiologically and may theoretically cause high-stress concentrations at the implant-vertebra interface.…”
Section: Introductionmentioning
confidence: 99%
“…11 [34]. Restoring a more physiological COR in the frontal plane may allow for restoration of a more physiological kinematic in axial rotation and lateral bending and theoretically limiting uncovertebral and facet kinematic conflicts during these motions [35,36]. In fact, TDR with caudal centre of rotation is more suitable during FE motion, whereas TDR with cranial centre of rotation is preferred during lateral bending and axial rotations.…”
Section: Kinematicsmentioning
confidence: 99%